EP412 Fertility sparing surgery of >2 cm cervical cancer following neo-adjuvant chemotherapy: a 12-year experience in a single tertiary care center. (1st November 2019) - Tesfai, F; Kroep, J; Nout, R; Gaarenstroom, K; de Kroon, C; van Loenhout, R; Smit, V; Trimbos, J; van Poelgeest, M; Beltman, J
Abstract : Introduction/Background: To assess feasibility, safety and clinical outcomes (recurrence, obstetric outcomes) in patients with cervical tumors >2 cm treated with neoadjuvant chemotherapy in preparation for fertility sparing surgery (FSS). In addition, to investigate predictive variables in these patients. Methodology: A retrospective analysis of patients was conducted in patients who were selected to receive upfront chemotherapy before fertility sparing surgery. Surgical and clinical outcomes were examined in relation to radiological and pathological results. In addition, obstetrical outcomes were investigated. We compared our results with other case series in literature. Results: A total of 20 women were treated with neo-adjuvant chemotherapy for >2 cm cervical tumors at our institution. Mean tumor size was 4, 4 cm. Chemotherapy consisted of 6 weekly cycles of cisplatin and paclitaxel. In 15 of 20 cases (75%) fertility was successfully preserved. In 5 of 20 cases FSS failed: 2 of 20 patients had stable disease after 3 cycles and did not meet criteria for surgery and 3 patients had intra- or postoperative indication for adjuvant therapy. Four relapses occurred in total of whom 3 died. Two of these were in the group of the successful ART. Therefore, fertility is currently preserved in 13 patients. Eight spontaneous pregnancies in 3 women occurred with six babies born at term. Conclusion: Neo-adjuvant chemotherapy followed by FFS is feasible and save option in in selected patients with cervical tumors >2 cm. Unfavorable prognostic factors are defined which can help in patients selection for FSS. Disclosure: Nothing to disclose.